Fibrolipoma of the hard palate: an uncommon location. Case report - Flores-Alvarado, Sergio Alberto; Olguín-Villarreal, Luis Mario; Rumayor-Piña, Alicia; Vargas-Segura, Alejandra Isabel; Flores-Flores, Diana Antonieta (Revista Facultad de Odontología Universidad de Antioquia, 2022)
Fibrolipoma, a benign soft tissue adipose tumor, is a histological variant of lipoma. Clinically, it presents as a painless slow-growing mass, indistinguishable from other benign soft tissue tumors. In the oral cavity, it is mainly encountered in the buccal mucosa. Involvement of the palate is very rare; it accounts for around 7-14% of all oral fibrolipomas. In this article, we describe a case of fibrolipoma in the hard palate of a 70-year-old female, who presented with an asymptomatic pedunculated mass, characterized by a normal-colored and smooth surface, which have been present for 20 years. The lesion was excised, and histopathological study revealed a fibrolipoma. To the best of our knowledge, only 17 cases occurring in the palate have been reported in the literature. Since fibrolipoma presents clinical similarities with other benign soft tissue neoplasms, a thorough clinical examination and histopathological analysis are essential for obtaining diagnosis.